Secondary neutron dose contribution from pencil beam scanning, scattered and spatially fractionated proton therapy. (24th November 2021) - Leite, A M M; Ronga, M G; Giorgi, M; Ristic, Y; Perrot, Y; Trompier, F; Prezado, Y; Créhange, G; De Marzi, L
Abstract: The Orsay Proton therapy Center (ICPO) has a long history of intracranial radiotherapy using both double scattering (DS) and pencil beam scanning (PBS) techniques, and is actively investigating a promising modality of spatially fractionated radiotherapy using proton minibeams (pMBRT). This work provides a comprehensive comparison of the organ-specific secondary neutron dose due to each of these treatment modalities, assessed using Monte Carlo (MC) algorithms and measurements. A MC model of a universal nozzle was benchmarked by comparing the neutron ambient dose equivalent, H *(10), in the gantry room with measurements obtained using a WENDI-II counter. The secondary neutron dose was evaluated for clinically relevant intracranial treatments of patients of different ages, in which secondary neutron doses were scored in anthropomorphic phantoms merged with the patients' images. The MC calculated H *(10) values showed a reasonable agreement with the measurements and followed the expected tendency, in which PBS yields the lowest dose, followed by pMBRT and DS. Our results for intracranial treatments show that pMBRT yielded a higher secondary neutron dose for organs closer to the target volume, while organs situated furthest from the target volume received a greater quantity of neutrons from the passive scattering beam line. To the best of our knowledge, this is the first study to compare MC secondary neutron dose estimates in clinical treatments between these various proton therapy modalities and to realistically quantify the secondary neutron dose contribution of clinical pMBRT treatments. The method established in this study will enable epidemiological studies of the long-term effects of intracranial treatments at ICPO, notably radiation-induced second malignancies.